Pre-arterialization of coronary veins prior to retroperfusion of ischemic myocardium: percutaneous closure device - Choy, Jenny S.; Hubbard, Terry; Golts, Eugene M.; Bhatt, Deepak L.; Navia, José A.; Kassab, Ghassan S. (Frontiers in Cardiovascular Medicine, 2023)
Background-Chronic coronary retroperfusion to treat myocardial ischemia has previously failed due to edema and hemorrhage of coronary veins suddenly exposed to arterial pressures. The objective of this study was to selectively adapt the coronary veins to become arterialized prior to coronary venous retroperfusion to avoid vascular edema and hemorrhage.Methods and results-In 32 animals (Group I=19 and Group II=13), the left anterior descending (LAD) artery was occluded using an ameroid occlusion model. In Group I, the great cardiac vein was blocked with suture ligation (Group IA=11) or with occlusion device (Group IB=8) to arterialize the venous system within 2 weeks at intermediate pressure (between arterial and venous levels) before a coronary venous bypass graft (CVBG) was implemented through a left internal mammary artery (LIMA) anastomosis. Group II only received the LAD artery occlusion and served as control. Serial echocardiograms showed recovery of left ventricular (LV) function with this adaptation-arterialization approach, with an increase in ejection fraction (EF) in Group I from 38±5% after coronary occlusion to 53±7% eight weeks after CVBG, whereas in Group II the EF never recovered (41±2% to 33±7%). The remodeling of the venous system not only allowed restoration of myocardial function when CVBG was implemented but possibly promoted a novel form of "collateralization" between the native arterioles and the newly arterialized venules, which revascularized the ischemic myocardium.Conclusions-These findings form a potential rationale for a venous arterializationrevascularization treatment for the refractory angina and the "no-option" patients using a hybrid percutaneous (closure device for arterialization)/surgical approach (CVBG) to revascularize the myocardium.